UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN ASAM JAWA (Tamarindus indica L) TERHADAP BAKTERI Propionibacterium acne DAN BAKTERI Pseudomonas aeruginosa - Irawan, Ade; Ulfah, Mariam; Fadillah, Aulia Nur Indri (STIKes Muhammadiyah Kuningan, 2023)
The goal of this research is to find out the capability of tamarind leaf ethanol extract (Tamarindus indica Linn) to inhibit the maturationof Propiomibacterium acnes and Pseudomonas aeruginosa bacteria as well as the optimal concentration of tamarind leaf extract that can do so. Using 96% ethanol as a solvent, maceration was used for extraction. Antibacterial activity testing uses the agar diffusion method by means of discs. According to studies on the antibacterial action of tamarind leaf ethanol extract opposed tothe bacteria Propionibacterium acne and Psedomonas aeruginosa, at a concentration of 20%, the extract can already block the development of bacteria in the medium range, while at a concentration of 80%, the extract can inhibit bacterial growth in the strong category. The one-way anova method and the LSD test were used to examine the antibacterial activity test findings. According to Anova data, the test bacteria were suppressed at doses of 20%, 40%, 60%, & 80%. Effective concentrations to inhibit Propionibacterium acne bacteria and Pseudomonas aeruginosa bacteria at concentrations of 20%, 40%, 60%, & 80%. The measurement of the area of bacterial growth inhibition increases with tamarind leaf extract concentration. Flavonoids, alkaloids, saponins, tannins, and steroids can be found in tamarind leaf ethanol extract. Tamarind leaf ethanol extract has antibacterial activity against Propionicaterium acne and Pseudomonas aeruginosa bacteria and has an inhibition zone at 80% concentration with an average diameter of 25.83 cm and 17.66 cm.